Spatial and temporal variability of environmental proxies from the top 120 m of two ice cores in Dronning Maud Land (East Antarctica) - S. Wauthy; J.-L. Tison; M. Inoue; S. El Amri; S. Sun; F. Fripiat; P. Claeys; F. Pattyn (Earth System Science Data, 2024)
The Antarctic ice sheet's future contribution to sea level rise is difficult to predict, mostly because of the uncertainty and variability of the surface mass balance (SMB). Ice cores are used to locally (kilometer scale) reconstruct SMB with a very good temporal resolution (up to sub-annual), especially in coastal areas where accumulation rates are high. The number of ice core records has been increasing in recent years, revealing an important spatial variability and different trends of SMB, highlighting the crucial need for greater spatial and temporal representativeness. We present records of density, water stable isotopes ( δ 18 O , δ D , and deuterium excess), major ions concentrations ( Na + , K + , Mg 2+ , Ca 2+ , MSA, Cl − , SO 4 2 - <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="29pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="06a1e144313624090049b6627390d3e8"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="essd-16-35-2024-ie00001.svg" width="29pt" height="17pt" src="essd-16-35-2024-ie00001.png"/></svg:svg> , and NO 3 - <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="dd23f13eb24280cbe650be4567ce8571"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="essd-16-35-2024-ie00002.svg" width="25pt" height="16pt" src="essd-16-35-2024-ie00002.png"/></svg:svg> ), and continuous electrical conductivity measurement (ECM), as well as age models and resulting surface mass balance from the top 120 m of two ice cores (FK17 and TIR18) drilled on two adjacent ice rises located in coastal Dronning Maud Land and dating back to the end of the 18th century. Both environmental proxies and SMB show contrasting behaviors, suggesting strong spatial and temporal variability at the regional scale. In terms of precipitation proxies, both ice cores show a long-term decrease in deuterium excess (d-excess) and a long-term increase in δ 18 O , although less pronounced. ...